Processo civil e direitos humanos: o controle de convencionalidade no processo civil - Fonsêca, Vitor Moreira da (2018)
Despite the importance of the conventionality control by the Inter-American Court of Human Rights, little is known about the relation between civil procedure and human rights. This study shows how the conventionality control may affect civil procedure. It analyzes the case-law of the Inter-American Court about the articles 8 (right to a fair trial) and 25 (right to judicial protection) of the American Convention on Human Rights and how it applies to civil procedure. Based on the most important cases of the Inter-American Court, it proposes a type of conventionality control in Brazilian civil procedure. In the end, the final chapter discusses some impacts of the results in Brazil